Diseño de un sistema de producción de hidrógeno verde utilizando energía fotovoltaica. - Tisalema Til, Franklin Elías (2022)
This research aimed to study renewable energies, focusing on an alternative storage system. It was proposed to generate hydrogen by electrolysis of water, to be stored and used to generate electricity through a hydrogen engine. The hydrogen production plant (PPH) will use a system composed of photovoltaic panels as an energy source. In this context, the development of a methodology for the design of the different stages and choice of the main elements that compose a hydrogen plant was proposed, as well as the dimensioning of a photovoltaic system to guarantee the production of green hydrogen.